Key indicators for Asia and the Pacific 2018. (Key Indicators for Asia and the Pacific., 2018)
The Key Indicators (KI) 2018 presents the latest statistics on a comprehensive set of economic, financial, social, environmental, and SDG indicators for the 48 regional members of the Asian Development Bank (ADB). It is designed to serve as a resource for information on development issues across the region for a wide audience, including policy makers, development practitioners, government officials, researchers, students, and the general public. This years Key Indicators publication is accompanied by a special supplement focusing on Technological Innovation for Agricultural Statistics. It presents results from a recently concluded statistics capacity building project of the ADB, showcasing the importance of remotesensing technology to enhance the quality of paddy rice area, yield, and production statistics.